Knowledge, Awareness, and Attitudes Regarding 3D Printing Materials in Prosthodontics Among Dental Students: A Multi-Center Cross-Sectional Study in Libya - Elnaili, Salma (Libyan Journal of Medical and Applied Sciences, 2026)
Three-dimensional (3D) printing has become an essential component of modern prosthodontics, offering improved accuracy, efficiency, and customization. However, its effective clinical implementation depends on adequate knowledge of printing materials among dental students. This study aimed to assess the knowledge, awareness, and attitudes of dental students regarding 3D printing materials in prosthodontics in Libya. A multi-center descriptive cross-sectional study was conducted among undergraduate dental students and interns from public and private universities in Libya between March and April 2026. Data were collected using a structured self-administered questionnaire. A total of 201 responses were analyzed using SPSS version 23. Descriptive statistics and Chi-square tests were applied, with statistical significance set at p < 0.05. Participants demonstrated moderate levels of knowledge and awareness regarding 3D printing in dentistry. While 78.1% recognized its applications in prosthodontics, more than half were unable to identify specific materials used. Resin and acrylic-based materials were the most commonly recognized. Nearly half of the participants expressed uncertainty regarding material safety and mechanical properties. Despite these gaps, the majority (93%) showed a positive attitude and interest in learning more about digital dentistry. Clinical level and attendance of educational courses were significantly associated with higher knowledge and awareness (p < 0.05). The findings highlight gaps in material-specific understanding and emphasize the need for structured integration of digital dentistry education into undergraduate curricula.